Female Labor Force Participation in Bangladesh : What Do We Know? How Can We Address it in Operations? - World Bank Group (World Bank, Washington, DC, 2020)
This knowledge note is designed to support operational teams to design interventions to help address the challenges of female labor force participation in Bangladesh. The note presents a brief overview of the status and dynamics of female labor force participation in Bangladesh, along with a discussion of underlying causes. It identifies potential areas for investment and policy intervention and provides good practice case examples from World Bank projects around the world.